Determination of the Power Systems Operating According to the Lactic Acid in the Blood for shooters of Air Weapons (rifle/ pistol) Shooters - AbdulHameed, Ghusoon Natiq; Ali, Doaa Hussain (International Journal of Psychosocial Rehabilitation, 2020)
The sport of shooting is one of the fixed endurance sports, which depends on onion it's performance and competition to on enduring withstand the competition time (1.5) hours and the weight of the weapon, indicating that the sport of shooting carries the capacity of physical, functional and mental capacities, There is no doubt that working in them its operational work is subject to energy systems such as like any specific physical effort limited in time and which may interfere with the anaerobic system and aerobic system. The importance of this research is toiles in conducting an analytical study on the determination of the ratios of working systems by identifying the percentages of lactic acid in the blood before the competition in the middle and after the completion of competition (identify the ratios according to the Time of competition). The research problem of research is the decline of the performance and achievement levels of the men and women shooters in the middle and the end of the competition, where failures appear clearly in the shooters in the last 10 throws on the target, which led the researcher to study this problem. The objective of the research is to identify the energy systems employed by the shooters of the air weapons (men/women) and to identify the percentages of the lactic acid in the blood before, in the middle and after the competition, as well as to identify the relationship of these ratios percentages with the results of the competition. Methodology: The researcher used the descriptive method. The research procedures in the selection of the sample of the research in a comprehensive inventory inclusive method were (52) of the shooters of air weapons (pistol/rifle) participating in the Iraqi club's championship, the sample represented the whole society entire population. After the researcher conducted the pilot experiment two days before the competition, she conducted the main experiment on the same day of competition in relation to the lactic ratios before, in the middle and after completion. The two researchers concluded: The increase in the ratio of lactic acid in the research sample between the pre-test and the middle test, tribal, middle, for the middle test, and between the middle intermediate test and the post-text in favor of the post-test, and post-secondary gradually, and there is a reverse correlation between the ratios of lactic acid and achievement. The two researchers recommended that trainers be instructed to develop plans and training programs for shooting according to the working energy systems, taking into consideration the results of the current study.